Evaluation of Tolerance and Reduction Capabilities of Some Bacterial Isolates to Lead (Bangladesh Journal of Scientific and Industrial Research, 2025)
Lead contamination from mining activities poses significant environmental and health risks, necessitating effective remediation strategies. This study evaluates the lead tolerance and reduction capabilities of five bacterial isolates—Pseudomonas aeruginosa strain A3, Bacillus paraflexus strain rnr13, Providentia stuartii strain MF1, Pantoea agglomerans, and Commamonas thioxydans strain MA1, sourced from lead-contaminated effluents in Ikwo L.G.A, Ebonyi State, Nigeria. Effluent samples were collected from two mine sites and a discharge point, and bacterial tolerance to lead concentrations (100–300 mg/L) was assessed using Luria Bertani broth. Lead reduction was investigated under varying pH (2.5 and 5.2) and temperature (30°C, 37°C, and 45°C) conditions, with residual lead quantified via a colorimetric Dithizone method. Results revealed that P. aeruginosa A3, B. paraflexus rnr13, and P. stuartii MF1 exhibited increased growth with higher lead concentrations and time, while P. agglomerans and C. thioxydans MA1 showed reduced tolerance. Lead reduction was significantly enhanced at pH 5.2 and 45°C, with P. aeruginosa A3 and B. paraflexus rnr13 demonstrating superior reduction capacities. Statistical analysis using ANOVA confirmed the significant influence of pH and temperature on lead reduction (p < 0.05). These findings underscore the potential of indigenous lead-tolerant bacteria for bioremediation of contaminated mine effluents, advocating for their use in consortium-based strategies to mitigate heavy metal pollution under optimized environmental conditions.Bangladesh J. Sci. Ind. Res. 60(3), 131-142, 2025